A Novel Operationalization Approach in Generation Phenomenon: Insights and Implications from Turkey’s Generational Dynamics - Osman Çevik; Umut Çil (Journal of Economy Culture and Society)
As scholarly interest in generational studies grows, so too does the scrutiny surrounding the phenomenon's validity. This study addresses both the burgeoning interest and skepticism by proposing an innovative operationalization of generations within the context of Turkey, aiming to introduce new concepts and methodologies to the field. While generational phenomena have often been approached with global or broadly applicable classifications, this research advocates for the consideration of national contexts as pivotal for accurate analysis. Using Turkey as a case study—identified through generations such as the Founders, Republican Generation, First Democrats, Military Coup Generation, First Neoliberals, and Social Media Generation—this study illustrates the application of the proposed operationalization. Conducted through a qualitative inquiry and informed by a multidisciplinary approach involving participants from various social sciences, this research not only names and defines these six generations but also elucidates their defining the initiator, finisher and internal turning points, the spheres of influence, the successor and predecessor members. Such analysis not only addresses existing criticisms but also enriches the discourse on generational dynamics in Turkey. The study emphasizes the critical need to refine operationalization strategies, thereby enhancing generational analysis's effectiveness.